Preventable stillbirths in India and Pakistan: a prospective, observational study. (19th July 2021) - Goldenberg, RL; Saleem, S; Goudar, SS; Silver, RM; Tikmani, SS; Guruprasad, G; Dhaded, SM; Yasmin, H; Bano, K; Somannavar, MS; Yogeshkumar, S; Hwang, K; et al.
Abstract : Objective: Stillbirths occur 10–20 times more frequently in low‐income settings compared with high‐income settings. We created a methodology to define the proportion of stillbirths that are potentially preventable in low‐income settings and applied it to stillbirths in sites in India and Pakistan. Design: Prospective observational study. Setting: Three maternity hospitals in Davangere, India and a large public hospital in Karachi, Pakistan. Population: All cases of stillbirth at ≥20 weeks of gestation occurring from July 2018 to February 2020 were screened for participation; 872 stillbirths were included in this analysis. Methods: We prospectively defined the conditions and gestational ages that defined the stillbirth cases considered potentially preventable. Informed consent was sought from the parent(s) once the stillbirth was identified, either before or soon after delivery. All information available, including obstetric and medical history, clinical course, fetal heart sounds on admission, the presence of maceration as well as examination of the stillbirth after delivery, histology, and polymerase chain reaction for infectious pathogens of the placenta and various fetal tissues, was used to assess whether a stillbirth was potentially preventable. Main outcome measures: Whether a stillbirth was determined to be potentially preventable and the criteria for assignment to those categories. Results: Of 984 enrolled, 872 stillbirths at ≥20 weeks of gestation met the inclusion criteria and were included; of these, 55.5% were deemed to be potentially preventable. Of the 649 stillbirths at ≥28 weeks of gestation and ≥1000 g birthweight, 73.5% were considered potentially preventable. The most common conditions associated with a potentially preventable stillbirth at ≥28 weeks of gestation and ≥1000 g birthweight were small for gestational age (SGA) (52.8%), maternal hypertension (50.2%), antepartum haemorrhage (31.4%) and death that occurred after hospital admission (15.7%). Conclusions: Most stillbirths in these sites were deemed preventable and were often associated with maternal hypertension, antepartum haemorrhage, SGA and intrapartum demise. Tweetable abstract: Most stillbirths are preventable by better care for women with hypertension, growth restriction and antepartum haemorrhage. Tweetable abstract: Most stillbirths are preventable by better care for women with hypertension, growth restriction and antepartum haemorrhage.